Pertanggungjawaban Perdata atas Insiden Keselamatan di Terminal Bandar Udara - Agung Sofyan; Pristika Handayani; Alwan Hadiyanto (JURNAL USM LAW REVIEW, 2026)
This study aims to analyze the construction of civil liability for passenger losses arising from safety incidents at airport terminals and to determine the parties that may be held legally responsible. The research is motivated by the increasing risk of safety incidents in airport terminals as high-risk public facilities, accompanied by legal uncertainty regarding the distribution of liability among operational actors and the proportionality of compensation for victims. This condition creates an urgent need to formulate a liability framework that is not solely based on individual fault but also on risk allocation and systemic responsibility in public facility management. This research employs a normative juridical method using statutory, conceptual, and case approaches through doctrinal analysis of civil liability, consumer protection, and risk governance in high-risk public facilities. The novelty of this study lies in developing a multi-party liability model based on risk allocation that positions airport terminals as high-risk public facilities with heightened standards of duty of care. The findings show that civil liability includes material and immaterial compensation as well as the restoration of passenger rights and may be imposed on airport operators, airlines, and third parties individually or jointly and severally to ensure legal protection and justice for passengers. Penelitian ini bertujuan menganalisis konstruksi pertanggungjawaban perdata atas kerugian penumpang akibat insiden keselamatan di terminal bandar udara serta menentukan pihak-pihak yang dapat dimintai tanggung jawab hukum. Latar belakang penelitian ini adalah meningkatnya risiko insiden keselamatan di terminal sebagai fasilitas publik berisiko tinggi yang diiringi ketidakjelasan konstruksi tanggung jawab hukum, khususnya terkait distribusi tanggung jawab antarpelaku operasional dan proporsionalitas kompensasi bagi korban. Kondisi tersebut menimbulkan urgensi untuk merumuskan kerangka pertanggungjawaban yang tidak hanya berbasis kesalahan individual, tetapi juga berbasis alokasi risiko dan tanggung jawab sistemik dalam pengelolaan fasilitas publik. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan peraturan perundang-undangan, konseptual, dan kasus melalui analisis doktrin pertanggungjawaban perdata, perlindungan konsumen, serta pengelolaan risiko fasilitas publik berisiko tinggi. Kebaruan penelitian terletak pada pengembangan model pertanggungjawaban multipihak berbasis alokasi risiko yang menempatkan terminal bandar udara sebagai high-risk public facility dengan standar kewajiban kehati-hatian yang lebih tinggi. Hasil penelitian menunjukkan bahwa pertanggungjawaban perdata mencakup ganti rugi materiil, immateriil, serta pemulihan hak penumpang dan dapat dibebankan kepada pengelola bandar udara, maskapai penerbangan, dan pihak ketiga secara sendiri-sendiri maupun tanggung renteng guna menjamin perlindungan hukum dan keadilan bagi penumpang.
Keywords: Bandar Udara; Hukum Perdata; Keselamatan Penumpang; Pertanggungjawaban Perdata